Dynamic Behaviour of the Platform-vibrator with Soft Impact. Part 1. Dependence on Exciting Frequency - Bazhenov, V.A.; Pogorelova, O.S.; Postnikova, T.G.; Otrashevska, V.V. (Discontinuity, Nonlinearity, and Complexity, 2026)
Platform-vibrators are the main molding equipment in the production of precast concrete elements. It is designed for compaction and molding of concrete products. We have created a mathematical model of a platform-vibrator with shock which is used for the manufacture of large elements. The created model corresponds to a strongly nonlinear non-smooth discontinuous 2-DOF vibro-impact system with soft impact. The simulation of soft impact with linear force and nonlinear force corresponding to qusistatic contact Hertz law is compared. The analysis of dynamic behaviour when changing the exciting frequency is performed. The zones of periodic motion, hysteresis, transient chaos, and a boundary crisis on its right border are shown. The chaoticity of the movement is confirmed by the typical form of phase trajectories, Poincaré maps, Foureir spectra, the positive sign of Lyapunov exponent, the fractal structure of Poincaré map, and the specific form of wavelet coefficients surface and its projection.